Cloud-based mobile-retail application for textile cyberpreneurs : task-technology fit perspective analysis - Nik Zulkarnaen Khidzir; Wan Safra Diyana Wan Abdul Ghani; Tan Tse Guan (2017)
Cloud computing and mobile computing paradigms have enhanced the usage of current technology among people from various sectors to perform certain required tasks. The combination of these two paradigms have also created the existense of cloud-based mobile applications that are designed to be useful in business environments, such as to be used by textile cyberpreneurs for m-retail transaction. As cloud adoption was previously low among Malaysian entrepreneurs, the usage intention factors of related cloud technology and services should be determined for better clarification and future technology enhancements. Besides, studies on m-retail or m-shopping adoption in Malaysia were merely focused on customer's perspectives rather than retailer's perspectives. In measuring the suitability of Cloud-based M-Retail (CBMR) application with the task requirements of textile cyberpreneurs, Task-technology Fit (TTF) model is used as basis of this research.Results from a pilot study, through a surveyo selected group of textile cyberpreneurs shows instrument's reliability and positive feedbacks to support the intention to use the technology. The future direction of the study in which to apply the instruments to a larger group of respondents is also discussed along with its potential contribution